PENENERAPAN MODEL PEMBELAJARAN AUDITORY, INTELLECTUALLY, REPETITION (AIR) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI SELANGIT - Aryati Apriliah; Maria Luthfiana; Reny Wahyuni (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2019)
The purpose of this study was to determine the completeness of the mathematics learning outcomes of class VIII students of Selangit State Middle School 2017/2018 Academic Year after the Learning Model Auditory, Intellectually, Repetition (AIR) was applied. The type of research used is in the form of a quasi experiment. The population is all eighth grade students of Selangit Public Middle School, consisting of 126 students and as a sample are students of class VIII.4 consisting of 30 students. Data collection is done by test techniques, test data collected is analyzed using t-test. Based on the t-test analysis with a significant level of α = 0.05, tcount> ttable (2,821)> (1,699) was obtained, so it can be concluded that the mathematics learning outcomes of students after VIII Selangit Public Middle School after the implementation of the learning model Auditory, Intellectually, Repitition (AIR ) significant completion with the average test scores before the implementation of the learning model Auditory, Intellectually, Repetition (AIR) 22.15 and after 73.94 before the implementation of the learning model Auditory, Intellectually, Repetition (AIR).